2007
DOI: 10.1200/jco.2006.07.4807
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between O6-Methylguanine-DNA Methyltransferase and Survival in Inoperable Newly Diagnosed Glioblastoma Patients Treated With Neoadjuvant Temozolomide

Abstract: This dose-dense temozolomide regimen resulted in modest antitumor activity with an acceptable safety profile in the neoadjuvant setting, and expression of MGMT correlated with response to temozolomide. However, this treatment approach seems to be inferior to standard concomitant RT plus temozolomide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 23 publications
(17 reference statements)
8
127
0
2
Order By: Relevance
“…Some studies of high-grade glioma patients treated with alkylating agents, including GBM patients, have reported significant association of MGMT expression by IHC with patient outcome. [15][16][17][18] However, in other recent studies of cohorts of GBM patients treated by radiotherapy plus temozolomide, no correlation between MGMT expression and patient survival was found. 7,11,19 In this study, we compare the analytical performances and the predictive values of 5 techniques (MS-PCR, methylation-sensitive high-resolution melting, pyrosequencing, MethyLight, and IHC) for MGMT analysis in a series of 100 newly diagnosed GBM patients treated with temozolomide.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Some studies of high-grade glioma patients treated with alkylating agents, including GBM patients, have reported significant association of MGMT expression by IHC with patient outcome. [15][16][17][18] However, in other recent studies of cohorts of GBM patients treated by radiotherapy plus temozolomide, no correlation between MGMT expression and patient survival was found. 7,11,19 In this study, we compare the analytical performances and the predictive values of 5 techniques (MS-PCR, methylation-sensitive high-resolution melting, pyrosequencing, MethyLight, and IHC) for MGMT analysis in a series of 100 newly diagnosed GBM patients treated with temozolomide.…”
Section: Introductionmentioning
confidence: 90%
“…The staining was performed as previously described. 18 The percentage of positive tumor cells was determined by Dominique Figarella-Branger as follows. The percentage of the tumor immunoreactive nuclei was counted at high magnification.…”
Section: Immunohistochemistry For Mgmt Protein Analysismentioning
confidence: 99%
“…42,43 However, it is a predictive marker of a favorable outcome in patients with temozolomide-treated glioblastomas. [44][45][46][47] Temozolomide also reportedly enhances radiation responsiveness in MGMTnegative human glioblastoma cell lines. 48 …”
Section: Temozolomidementioning
confidence: 97%
“…The early studies that used immunofluorescence detection in malignant gliomas, 6,7 as well as more-recent studies in progressive low-grade oligodendroglial tumors 23 or newly diagnosed glioblastoma, 9 reported that low MGMT protein levels had predictive value for the response to alkylating agents. The clinical value of immunohistochemical detection of MGMT protein in human gliomas, however, remains controversial for several reasions.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…9 Decreased levels of MGMT protein can be attributed to epigenetic silencing mediated by MGMT gene promoter methylation, which can be assessed by a simple methylation-specific PCR (MSP). A correlation with survival was demonstrated when glioma patients were treated with nitrosoureas 10 or temozolomide, 11 strongly suggesting that MGMT promoter methylation assessment could provide a prognostic or predictive biomarker for benefit from alkylator-based chemotherapy added to radiotherapy.…”
mentioning
confidence: 99%